Assessment of Households’ Perception Towards Participatory Forest Management the Case of Heban Arsi Woreda, Ethiopia - Gonche Girma (Indonesian Journal of Environmental Management and Sustainability, 2022)
Understanding communities perceptions and attitudes towards participatory forest management (PFM) is crucial to successful PFM improvement. However, there is a lack of research evidence on the perception of local communities for PFM program intervention. The purpose of the study was to exmine local community perceptions and attitudes towards PFM intervention. In this study, 131 households were surveyed and data were collected through the household survey; key informant interviews (KIIs), focus group discussion (FGD). Descriptive statistics were used to analyze the data. Results show that the households perceived that there is no deforestation after PFM intervention. This increased species diversity, forest coverage, productivity of the forest, number of valuable species and address environmental degradation. Respondents that PFM program has opportunities to change a negative attitude to a positive through giving of power to the local community, enables to exclude non-PFM members, and creates a sense of belongingness to use and conservation of forest. The finding demonstrated that households generate their incomes from different sources and the share of forest income is the second. The different actions such as better protection of existing forests, access to alternative livelihood, access to better knowledge were suggested to increase the existing benefits and management of PFM. The finding of the study suggests further improvement of local communities’ perception and attitudes as well as providing alternatives to improve forest conditions and livelihood.